Canarium odontophyllum from Borneo Island: Phytochemistry, pharmacology, and modern applications - Gilbert Ringgit; Christine Gustin; Bo Eng Cheong; Muhammad Dawood Shah; Shafiquzzaman Siddiquee (Springer Nature, 2025)
Canarium odontophyllum, commonly known as dabai, is a seasonal indigenous fruit from Borneo (East Malaysia). It has been reported to have significant potential in pharmaceutical and modern applications; however, its full potential has yet to be thoroughly explored. Results Phytochemical studies have identified seven therapeutic properties in C. odontophyllum. Modern applications include its use as an alternative biofuel (e.g., cooking oil and biodiesel), chocolate production, a component in dye- sensitized solar cells, and in wastewater treatment. Conclusion C. odontophyllum contains a rich array of phytochemical compounds with potential applications in the pharmaceutical and engineering sectors. This review aims to encourage further research into phytochemistry, pharmacology, and modern applications.